53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-1046
|View full text |Cite
|
Sign up to set email alerts
|

Plume and Shock Interaction Effects on Sonic Boom in the 1-foot by 1-foot Supersonic Wind Tunnel

Abstract: The desire to reduce or eliminate the operational restrictions of supersonic aircraft over populated areas has led to extensive research at NASA. Restrictions are due to the disturbance of the sonic boom, caused by the coalescence of shock waves formed by the aircraft. A study has been performed focused on reducing the magnitude of the sonic boom N-wave generated by airplane components with a focus on shock waves caused by the exhaust nozzle plume. Testing was completed in the 1-foot by 1-foot supersonic wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The plume and shock interaction study was developed to collect data for CFD validation where a nozzle plume passed through the shock generated from the wing or tail of a supersonic vehicle. Major findings of the study demonstrated how the interaction of the jet plume caused a thickening, or widening [6], of the shock generated by the wedge or aft deck, and movement of the shock location with increasing nozzle pressure ratio. There were, however, some concerns with the data.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The plume and shock interaction study was developed to collect data for CFD validation where a nozzle plume passed through the shock generated from the wing or tail of a supersonic vehicle. Major findings of the study demonstrated how the interaction of the jet plume caused a thickening, or widening [6], of the shock generated by the wedge or aft deck, and movement of the shock location with increasing nozzle pressure ratio. There were, however, some concerns with the data.…”
Section: Introductionmentioning
confidence: 95%
“…The double wedge shock generator was a scaled-up version (1.5 times) of the shock generator used in the Glenn Research Center (GRC) 1x1 test [6], to allow for a similar test case between the two tests. The double wedge generated a strong shock, but it is not representative of a modern day horizontal tail design.…”
Section: B Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this tunnel's capability to test small-scale models was developed to validate results obtained for supersonic nozzle concepts 4 , it was chosen as the facility to obtain fundamental data on nozzle plume and shock interaction effects. The testing conducted used a simple jet flow and simulated tail shock generated by a wedge shaped shock generator.…”
Section: Introductionmentioning
confidence: 99%
“…The capability to test small-scale models in NASA GRC's 1-foot by 1-foot supersonic wind tunnel (1x1 SWT) was developed to validate results obtained for supersonic nozzle concepts. This capability was utilized for a fundamental study of the nozzle plume and shock interaction effects 11 . Analysis was performed on the experimental configuration using the Cart3D CFD code.…”
Section: Introductionmentioning
confidence: 99%